The Effect of Pregnancy Exercise on Reducing Back Pain in Third Trimester Pregnancy: Pengaruh Senam Hamil Terhadap Penurunan Nyeri Punggung pada Kehamilan Trimester III - Rif'atun Nisa; Ika Choirin Nisa; Ira Faridasari; Reka Agustina (Napande: Jurnal Bidan, 2022)
Background: Back pain is one of the most common discomforts felt by pregnant women in the third trimester. Most pregnant women at the Losarang Health Center experience back pain during their pregnancy. Pregnancy exercise is a form of exercise to strengthen and maintain the elasticity of the muscles of the abdominal wall, ligaments, and pelvic floor muscles associated with the delivery process. Purpose: To determine the effect of pregnancy exercise on reducing back pain in the third trimester of pregnancy. Methods: Quantitative with a quasi-experimental design and a pretest-posttest design approach. The population of third trimester pregnant women, at the Puskesmas Losarang, Indramayu in June-July 2021, amounting to 25 people. The sampling technique is total sampling. Pregnancy exercise intervention was carried out for 4 times. Data analysis in this research is univariate and bivariate. Bivariate analysis using t-test (t-test). The instrument used is the Observation Sheet and Pain Scale. Results: It is known that there was a decrease in the intensity of back pain for pregnant women before being given pregnancy exercise as many as 20 mothers (80%) experienced pain with severe intensity and after being given exercise for pregnant women it became 2 mothers (8%) and the intensity of mothers experiencing moderate pain was from 5 mothers (20%) to 22 mothers (88%).Conclusion: There is an effect of pregnancy exercise on reducing back pain in the third trimester of pregnancy. With this research, it is hoped that it can become a routine activity for the Public health center.